Physical Correlates of Torture Exposure in Karen Refugees. Issue 2 (17th February 2017) - Hoffman, Sarah J.; Robertson, Cheryl L.; Shannon, Patricia J.; Cook, Tonya L.; Letts, James; Mathiason, Michelle A.
ABSTRACT: We explored associations between torture history and physical health symptoms of 111 Karen refugees newly arrived to the United States. We conducted a retrospective cross-sectional analysis of electronic health data collected at the initial refugee health-screening exam. Unique to this analysis was the exploration of relationships between torture exposure, war trauma, and presenting physical and psychological health issues. We identified no unique effects of torture on physical health above and beyond trauma exposure. Overall, in our sample we found a high prevalence of underlying infectious conditions, pain, and hypercholesterolemia, regardless of torture exposure. We discuss effects of war trauma and torture experiences on physical exam findings and implications for future research.